2021
DOI: 10.1016/j.jamcollsurg.2021.07.687
|View full text |Cite
|
Sign up to set email alerts
|

Timing of Perioperative Pharmacologic Thromboprophylaxis Initiation and its Effect on Venous Thromboembolism and Bleeding Outcomes: A Systematic Review and Meta-Analysis

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…Whilst VTE risk necessitates chemoprophylaxis in the perioperative setting, strong evidence now exists demonstrating that chemoprophylaxis confers a clinically significant risk of bleeding [4]. Multiple studies now show that postoperative commencement of chemoprophylaxis is favored over pre‐ and intra‐operative administration because of reduced bleeding risk while preserving VTE protection [24, 26, 36–39]. In this study, our findings indicate that there is no optimal time window for initiating chemoprophylaxis in the early postoperative period.…”
Section: Discussionmentioning
confidence: 80%
“…Whilst VTE risk necessitates chemoprophylaxis in the perioperative setting, strong evidence now exists demonstrating that chemoprophylaxis confers a clinically significant risk of bleeding [4]. Multiple studies now show that postoperative commencement of chemoprophylaxis is favored over pre‐ and intra‐operative administration because of reduced bleeding risk while preserving VTE protection [24, 26, 36–39]. In this study, our findings indicate that there is no optimal time window for initiating chemoprophylaxis in the early postoperative period.…”
Section: Discussionmentioning
confidence: 80%
“…Additionally, within major abdominal surgery, subgroup analysis of patients with an inherently high thromboembolic risk also favours postoperative chemical thromboprophylaxis over early usage 21 . These reports, along with findings from two recent meta-analyses, one of randomized trials involving different surgical disciplines 22 , and the other of randomized trials and cohort studies involving major abdominal surgery 23 , demonstrated that postoperative chemical thromboprophylaxis did not diminish protection against VTE. Therefore, in the context of significant global variations in practice 4 , 24 , this study contributes to a growing body of evidence, spanning multiple specialties and procedural types, that postoperative chemical thromboprophylaxis is a safer approach for patients, resulting in a similar risk of VTE, but lower rates of bleeding.…”
Section: Discussionmentioning
confidence: 94%
“…In a recent meta-analysis, McAlpine et al8 investigated 17,124 patients from 22 studies exploring the impact of chemoprophylaxis timing on postoperative VTE and bleeding rates. They demonstrated no difference in VTE and bleeding rates between early and postoperative cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…McAlpine et al 8 recently conducted a meta-analysis on the timing of perioperative thromboprophylaxis across multiple surgical specialties. Notably, these authors combined data from orthopedic, thoracic, cardiac, breast, obstetric, and abdominal surgeries.…”
mentioning
confidence: 99%